2019
DOI: 10.1111/his.13989
|View full text |Cite
|
Sign up to set email alerts
|

Vulval squamous cell carcinoma and its precursors

Abstract: Vulval squamous cell carcinoma (VSCC) can arise through two distinct pathways [human papillomavirus (HPV)‐associated and HPV‐independent], and these VSCC variants are recognised as different disease entities on the basis of different aetiologies, morphological features, molecular events during oncogenesis, precursor lesions, prognosis, and response to treatment. The precursor of HPV‐associated VSCC, variously referred to as high‐grade squamous intraepithelial lesion (HSIL) [vulvar intraepithelial neoplasia (VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
115
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(130 citation statements)
references
References 51 publications
4
115
0
11
Order By: Relevance
“…Because dVIN is often difficult to recognize for patients as well as for clinicians, including pathologists, it may partly explain why so few patients have been diagnosed with dVIN 23,25,26 . Signs of dVIN can be variable and often subtle, leading to misdiagnoses and inadequate clinical care due to diagnostic delay, especially in centers with limited exposure to this rare disease 27‐29 . It has been shown that dVIN was missed in 42% of biopsies initially diagnosed as LS in a series of patients who developed VSCC 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Because dVIN is often difficult to recognize for patients as well as for clinicians, including pathologists, it may partly explain why so few patients have been diagnosed with dVIN 23,25,26 . Signs of dVIN can be variable and often subtle, leading to misdiagnoses and inadequate clinical care due to diagnostic delay, especially in centers with limited exposure to this rare disease 27‐29 . It has been shown that dVIN was missed in 42% of biopsies initially diagnosed as LS in a series of patients who developed VSCC 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The precursor lesion of VSCC is high‐grade vulvar intraepithelial neoplasia (VIN). VIN is classified into high‐grade squamous intraepithelial lesion (HSIL), which is human papillomavirus (HPV) related, and differentiated VIN (dVIN), which is independent of HPV and associated with lichen sclerosus 1‐3 . HSIL, previously known as usual type of VIN (uVIN), is the most common type of VIN, occurring mainly in women aged between 35 and 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no other study had reported this phenomenon. Someone suggested that the morphological features of HPVindependent and HPV-associated precursor lesions can overlap, based on HE Staining [7]. Perhaps, it can be used to explain that phenomenon in our case report.…”
Section: Discussionmentioning
confidence: 59%
“…DVIN, VAAD and DE-VIL were belong to the precursor lesions of HPV-independent VSCC [7]. DE-VIL show prominent acanthosis and papillomatosis, but minimal atypia.…”
Section: Discussionmentioning
confidence: 94%